Protecting High-Risk Atrial Fibrillation Patients with Multiple Comorbidities - Wan Ahmad, Wan Azman (International Journal of Human and Health Sciences (IJHHS), 2024)
Patients with atrial fibrillation (AF) are often at high risk due to advanced age and multiple comorbidities. Even though some cases appear asymptomatic, AF confers significant mortality and morbidity from stroke. This topic will emphasize the importance of holistic protection for vulnerable patients and highlight the evolving body of evidence of NOAC treatment for stroke prevention in AF patients with comorbidities. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S15